Esterification Of Ethanol And Acetic Acid Catalysed By Immobilized Candida Rugosa Lipase - Mohd Radzi, Nurul Adila (Universiti Sains Malaysia, 2021)
Ethyl acetate is a versatile ester used as solvent and diluents. The conventional esterification reaction of ethanol and acetic acid was catalysed by sulphuric acid, H2SO4. Enzyme is a sustainable approach for the esterification reaction to produce ethyl acetate. In this study, the esterification reaction of ethanol and acetic acid catalysed by immobilized candida rugosa lipase (CRL) in n-hexane was optimized. The free CRL was immobilized by physical adsorption on support, Amberlite XAD7 which resulted in specific activity of 0.13 U/mg. The effect of reaction time, temperature, substrate molar ratio and enzyme loading were studied. Maximum conversion of 88% was attained at 2 hours of reaction time, temperature of 50°C, acetic acid to ethanol ratio of 0.5 and enzyme loading of 80 U. Next, the kinetic modelling of bi-substrate enzymatic transesterification of ethyl butyrate was studied using secondary data from research paper. The data was fitted to the rate equation of the kinetic model using non-linear regression to obtain the kinetic parameter. Based on the Lineweaver-Burk double reciprocal plot, the transesterification reaction follows ping-pong bi-bi mechanism with competitive inhibition by ethyl caprate. The kinetic parameters obtained was, Vmax = 1.1918 M, Km,A = 0.0117 M, Km,B = 0.1674, Ki,A = 0.1091 M, and Ki,B = 0.0031.